Supplementation with a fish protein hydrolysate (Micromesistius poutassou): effects on body weight, body composition, and CCK/GLP-1 secretion - Vincenzo Nobile; Elisa Duclos; Angela Michelotti; Gioia Bizzaro; Massimo Negro; Florian Soisson (Food & Nutrition Research, 2016)
Background: Fish protein hydrolysates (FPHs) have been reported as a suitable source of proteins for human nutrition because of their balanced amino acid composition and positive effect on gastrointestinal absorption. Objective: Here, we investigated the effect of a FPH, Slimpro®, obtained from blue whiting (Micromesistius poutassou) muscle by enzymatic hydrolysis, on body composition and on stimulating cholecystokinin (CCK) and glucagon-like peptide-1 (GLP-1) secretion. Design: A randomized clinical study was carried out on 120, slightly overweight (25 kg/m2 ≤ BMI<30 kg/m2), male (25%) and female (75%) subjects. FPH was tested in a food supplement at two doses (1.4 and 2.8 g) to establish if a dose–effect relationship exists. Product use was associated with a mild hypocaloric diet (−300 kcal/day). Body composition (body weight; fat mass; extracellular water; and circumference of waist, thighs, and hips) and CCK/GLP-1 blood levels were measured at the beginning of the study and after 45 and 90 days of product use. CCK/GLP-1 levels were measured since they are involved in controlling food intake. Results: Treated subjects reported an improvement of body weight composition and an increased blood concentration of both CCK and GLP-1. No differences were found between the 1.4 and 2.8 g FPH doses, indicating a plateau effect starting from 1.4 g FPH. Conclusions: Both 1.4 and 2.8 g of FPH were effective in improving body composition and in increasing CCK and GLP-1 blood levels.